Anticancer Effects of Plasma-Activated Medium Produced by a Microwave-Excited Atmospheric Pressure Argon Plasma Jet. (31st July 2020) - Jo, Ara; Joh, Hea Min; Chung, Tae Hun; Chung, Jin Woong
Abstract : Cold atmospheric plasma (CAP) has been reported to have strong anticancer effects in vitro and in vivo . CAP has been known to induce apoptosis in most cancer cells by treatment to cells using direct and indirect treatment methods. There are many reports of apoptosis pathways induced by CAP, but for indirect treatment, there is still a lack of fundamental research on how CAP can cause apoptosis in cancer cells. In this study, we applied an indirect treatment method to determine how CAP can induce cancer cell death. First, plasma-activated medium (PAM) was produced by a 2.45 GHz microwave-excited atmospheric pressure plasma jet (ME-APPJ). Next, the amounts of various reactive species in the PAM were estimated using colorimetric methods. The concentration of NO2 – and H2 O2 in PAM cultured with cancer cells was measured, and intracellular reactive oxidative stress (ROS) changes were observed using flow cytometry. When PAM was incubated with A549 lung cancer cells, there was little change in NO2 – concentration, but the concentration of H2 O2 gradually decreased after 30 min. While the intracellular ROS of A549 cells was rapidly increased at 2 hours, there was no significant change in that of PAM-treated normal cells. Furthermore, PAM had a significant cytotoxic effect on A549 cells but had little effect on normal cell viability. In addition, using flow cytometry, we confirmed that apoptosis of A549 cells occurred following flow cytometry and western blot analysis. These results suggest that among various reactive species produced by PAM, hydrogen peroxide plays a key role in inducing cancer cell apoptosis.